English as a second language (ESL) writing instructions and the effects on primary students: a multiple case study - Palpanadan, Sarala @ Thulasi; K Ravana, Venosha (Science and Engineering Research Support Society, 2020)
English as a second language (ESL) writing instruction is a challenging task for teachers. Writing lessons need to be prepared adequately by deciding on the right approach to be employed as the instructional methods influence students’ learning greatly. This study investigates the preferred teaching practices (between the product and process approach) of 10 pre-service teachers’ in teaching writing and the effects on students’ written texts. The data were collected from observations, semi-structured interviews and students’ written texts. The data from the observation checklists were analyzed using Rasch Measurement Model which validated the study with a high value of alpha Cronbach (0.81). Thematic and textual analyses were conducted on participants’ views and the students’ written text respectively. The findings revealed that product approach was the preferred practice. Consequently, the students’ prepared very identical pattern of written work based on the participants’ input. The students were able to prepare the written work with linguistic accuracy but did not show attempt to write more creatively. Thus, this study recommends teachers to integrate process approach strategies into their writing instructions to guide students to write more profoundly in future.